(5)(-2)+(5)(-2)(-3)=

Simple and best practice solution for (5)(-2)+(5)(-2)(-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5)(-2)+(5)(-2)(-3)= equation:


Simplifying
(5)(-2) + (5)(-2)(-3) = 0

Multiply 5 * -2
-10 + (5)(-2)(-3) = 0

Multiply 5 * -2
-10 + -10 * -3 = 0

Multiply -10 * -3
-10 + 30 = 0

Combine like terms: -10 + 30 = 20
20 = 0

Solving
20 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 20+-8x+30+-16x=180 | | -7r+6t-8s-r+12s+4t-t+2s-r= | | 6×12/2 | | -7x+4x+7+4x=(0-14)-(-8+5) | | 5-4(1-x)=21 | | 8x^2y^3z-2xyz+4x^3yz^2= | | -34(14x)+27(21x)=(75-75)+(-823+95) | | 2-x=-2(3x+4) | | 2X/3=3 | | 6x=(8-.25x)-(6-0.75x) | | (-4,3)M,=1/2 | | X/7=9=15 | | 2w=10+7w | | 3x^2-8xy+4y^2=6 | | 4x^2+378x-13631=0 | | 5+4h=9h | | 3(Mt+2)=7(4t+6) | | 50/6.25 | | 3x=(8-0.25x)-(3-.75x) | | 5/3*60 | | 2z+10=z | | 3(x+2)-4=2(4) | | ln(-1/2) | | -x+13=2x+1 | | 2c+3=50c-6 | | 6-5c=-4c | | -2a+3=9 | | 3(0)-9(3)=15 | | 2n-5=4n-7 | | 48=4n-4 | | 8a+18=6a+30 | | 4x^2+378x-4248.5=0 |

Equations solver categories